Global exponential stability of discrete-time neural networks with time-varying delays - S. Udpin (2018)
This paper presents some global stability criteria of discrete-time neural networks with time-varying delays. Based on a discrete-type inequality, a new global stability condition for nonlinear difference equation is derived. We consider nonlinear discrete systems with time-varying delays and independence of delay time. Numerical examples are given to illustrate the effectiveness of our theoretical results. © 2013 S. Udpin and P. Niamsup.